2006
DOI: 10.1007/s10891-006-0089-y
|View full text |Cite
|
Sign up to set email alerts
|

Influence of size effects on the critical diameter and growth of nanoparticles

Abstract: UDC 541.182The effect exerted by the dependence between the condensation and surface-tension coefficients and the size of an aerosol nanoparticle on its growth and critical diameter is investigated theoretically.Investigation of the characteristic features of transfer processes in aerosol systems with nanosized particles is of interest both for description of the atmospheric phenomena related to the formation and growth of water drops in the atmosphere [1] and for the technological processes where nanoparticle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 7 publications
0
1
0
Order By: Relevance
“…Surface tension itself increases with decreasing particle diameter below the Tolman length 50,51 . Furthermore with decreasing particle diameter, the deliquescence relative humidity and efflorescence relative humidity increases [52][53][54] , the equilibrium hygroscopic growth factor decreases 55 , the condensation coefficient of the gas molecule to the particle surface decreases 56 , and liquid-liquid phase separation is suppressed [57][58][59][60] . Virtanen et al 23,61 showed that the bounce factor of organic particles produced by OH dominated oxidation of pine emitted volatile organic compounds sharply decreases for particles with D < 30 nm , but not for solid ammonium sulfate particles.…”
mentioning
confidence: 99%
“…Surface tension itself increases with decreasing particle diameter below the Tolman length 50,51 . Furthermore with decreasing particle diameter, the deliquescence relative humidity and efflorescence relative humidity increases [52][53][54] , the equilibrium hygroscopic growth factor decreases 55 , the condensation coefficient of the gas molecule to the particle surface decreases 56 , and liquid-liquid phase separation is suppressed [57][58][59][60] . Virtanen et al 23,61 showed that the bounce factor of organic particles produced by OH dominated oxidation of pine emitted volatile organic compounds sharply decreases for particles with D < 30 nm , but not for solid ammonium sulfate particles.…”
mentioning
confidence: 99%